Perlindungan Hukum Bagi Pemegang Hak Merek Atas Persamaan Pada Pokoknya Berdasarkan Undang-Undang No. 20 Tahun 2016 Dalam Putusan MA No. 796 K/Pdt.Sus-Hki/2023 - Prasaja, Farisa Awanis; Mardianto, Agus; Afwa, Ulil (Lembaga Penelitian Pengabdian Masyarakat dan Pusat Kajian - Universitas Ngurah Rai, 2024)
This research discusses the Legal Protection for Trademark Rights Holders for Similarities in Principal Based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications in Supreme Court Decision No. 796 K/Pdt.Sus-Hki/2023 with Linda Anggraeningsih and Muhammad Shakeel as the Plaintiff and Defendant Parties and the legal consequences of the decision for the parties. The purpose of this research is to analyze whether the parties have received legal protection as trademark rights holders and also the legal consequences arising from the Supreme Court's decision. This research uses a normative juridical research approach method that relies on secondary data obtained through literature studies with qualitative normative methods. The results of research and discussion in this study can be concluded that Linda Anggraeningsih has not received legal protection for her Trademark Rights because the lawsuit she won in the Commercial Court was canceled by the Cassation Decision. Supreme Court Decision Number 796 K/Pdt.Sus-HKI/2023 canceled Decision Number 3/Pdt.Sus-Merek/2023/PN.Niaga.Jkt.Pst which results in Umamascarves Trademark is still entitled to produce and market its products because it remains validly registered in PDKI so that it gets legal protection for its trademark.